2017
DOI: 10.1038/mi.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolite activation of the aryl hydrocarbon receptor regulates IL-10 receptor expression on intestinal epithelia

Abstract: IL10 is a potent anti-inflammatory cytokine that inhibits the production of pro-inflammatory mediators. Signaling by IL10 occurs through the IL10 receptor (IL10R), which is expressed in numerous cell types, including intestinal epithelial cells (IEC), where it is associated with development and maintenance of barrier function. Guided by an unbiased metabolomics screen, we identified tryptophan (Trp) metabolism as a major modifying pathway in IFN-γ-dominant murine colitis. In parallel, we demonstrated that IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 61 publications
7
109
0
2
Order By: Relevance
“…[24][25][26][27] More recently, IN has been shown to improve dextran sulfate sodium-induced colitis in a mouse model via an AhR/IL-22-mediated pathway. 28 However, recent studies have also shown other mechanisms of AhR signaling in terms of the induction of IL-10 receptor expression on intestinal epithelia, 29 IL-10 production in macrophages, 30 the induction of regulatory T cells, 31 and the negative regulation of the NLRP3 inflammasome. 32 Regardless, IN with different mechanisms from the current standard treatments may be beneficial for cases in which the efficacy of immunosuppressant or biologics is inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] More recently, IN has been shown to improve dextran sulfate sodium-induced colitis in a mouse model via an AhR/IL-22-mediated pathway. 28 However, recent studies have also shown other mechanisms of AhR signaling in terms of the induction of IL-10 receptor expression on intestinal epithelia, 29 IL-10 production in macrophages, 30 the induction of regulatory T cells, 31 and the negative regulation of the NLRP3 inflammasome. 32 Regardless, IN with different mechanisms from the current standard treatments may be beneficial for cases in which the efficacy of immunosuppressant or biologics is inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-derived IL-10 was shown to activate CREB signaling in intestinal epithelial cells, leading to the secretion of the WNT1-inducible signaling protein 1, which in turn induced epithelial cell proliferation and wound closure (Quiros et al, 2017). Furthermore, up-regulation of the IL-10R in intestinal epithelial cells has been described (Kominsky et al, 2014), and recent studies not only confirm the importance of the IL-10R in wound healing but also implicate tryptophan metabolites and AhR in its up-regulation (Lanis et al, 2017).…”
Section: Nonclassic Roles Of Il-10mentioning
confidence: 96%
“…In colitis, these lymphocytes can then be transdifferentiated back toward Th1 cell types by Kyn signaling through AHR and contribute to the resolution of inflammation [75, 76]. Further contributing to resolution is the AHR induced expression of the IL-10 receptor (IL-10R1) on colonic epithelial cells [77]. IL-10 signaling is critical for colonic homeostasis and IL-10R1 expression on colonic epithelial cells helps regulate barrier formation [78].…”
Section: Tryptophan Metabolism and Intestinal Inflammationmentioning
confidence: 99%
“…IL-10 signaling is critical for colonic homeostasis and IL-10R1 expression on colonic epithelial cells helps regulate barrier formation [78]. Recent evidence demonstrates that exogenous Kyn enhances wound healing in an IL-10 dependent manner in vitro and alleviates DSS colitis in vivo [77]. …”
Section: Tryptophan Metabolism and Intestinal Inflammationmentioning
confidence: 99%